Innovation and Lean Production - Drahoš Vaněček (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2018)
Production has undergone historically through different changes, the essence of which is innovation. Innovations are either the introduction of new and more powerful machines and technologies, or just tiny, but everyday changes called Kaizen. The article focuses on the implementation of this second group of rationalization changes. 90 enterprises were surveyed and the results were evaluated mainly in terms of their size (small, medium, large), industry (engineering, electro-technical production, production of food, production of products for domestic use), and ownership of the company and by the importance in the supply chain. Regardless their size, the enterprises expect to continue the current trend with increasing demand and therefore they expect to expand the production employing more workers. New technology is supposed to be implemented to a lesser extent, but the situation is significantly better for the enterprises with a foreign owner. In small enterprises there is usually the absence of standards, which is a prerequisite for successful planning. Tailor-made production according to individual customer requirements exists mostly in greater enterprises. Regarding different types of waste reduction, defects are reported to be the most important issue, followed by motion, over-production and waiting. The research of 90 enterprises shoved, that most of them are not getting ready in a particular way for the future, although it might not be as favourable as it is now. Enterprises should increase the share of products with higher added value.